2018
DOI: 10.7759/cureus.3114
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Pakistani Medical Students’ Career Preference for General Practice Residency Training

Abstract: BackgroundFew studies have explored factors affecting preference of medical students towards general practice as a career choice. We conducted a survey in Karachi across various public and private sector medical colleges to examine factors associated with students’ general practice career aspirations in Karachi, Pakistan.MethodsFrom January to March 2018, we distributed a 21-item questionnaire to final year medical students in eight medical schools. The survey asked students about their top three career prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…In France, another study showed that about 20% of students chose a career in PHC after graduation 19 . In Pakistan, the result was similar to the present study: in a survey of 1,400 final-year medical students, in eight medical schools, it was verified that 24.1% of the respondents reported an interest in working in PHC 20 .…”
Section: Discussionsupporting
confidence: 89%
“…In France, another study showed that about 20% of students chose a career in PHC after graduation 19 . In Pakistan, the result was similar to the present study: in a survey of 1,400 final-year medical students, in eight medical schools, it was verified that 24.1% of the respondents reported an interest in working in PHC 20 .…”
Section: Discussionsupporting
confidence: 89%
“…2003 [32] USA (O) QT 111 Forth year 69.0% 60.8% NA 14 Good Barber S. 2018 [33] UK (O) QT & QL 280 Final and penultimate years 89.0% 51.0% NA 14 Good Bien A. 2019 [34] Germany (O) QT 361 Fourth, fifth or final year 70.9% 33.4% NA 12 Average Bilal M. 2018 [35] Pakistan (NO) QT 1400 Final year 100% 33.0% 24 14 Good Chen YC. 2014 [36] Taiwan (NO) QT 405 Interns 91.4% 59.4% 26.81 (3.44) 17 Very good Correia Lima de Souza L. 2015 [37] Brazil (NO) QT 1225 Medical students and doctors 79.2% 37.5% 24 14 Good Diderichsen S. 2013 [38] Sweden (O) QT 372 Final year 89.0% 42.0% 27.5 15 Good Du J.…”
Section: Resultsmentioning
confidence: 99%
“…Na França, outro estudo evidenciou que cerca de 20% dos estudantes escolheram uma carreira na APS após a graduação 19 . No Paquistão, o resultado foi similar ao presente estudo: em uma pesquisa com 1.400 estudantes de Medicina do último ano, em oito escolas de Medicina, identificou-se que 24,1% dos entrevistados referiam o interesse em atuar na APS 20 .…”
Section: Métodosunclassified
“…Outros fatores não avaliados neste trabalho são descritos na literatura como influências positivas na intenção de carreira em APS, como: comprometimento e atitudes empáticas 25,40 , interações com pacientes, profissionais da saúde 28,41 e comunidade 20,41,42 , questões financeiras 41,42 , bom equilíbrio entre vida profissional e pessoal 42,43 , valorização das relações médico-paciente de longo prazo 18,28,43 , prestar cuidados em diferentes fases de vida 18,42 , vivenciar atendimentos em área rural 5,18 e possibilidade de atuar com medicina preventiva 20 .…”
Section: Métodosunclassified